Analyses of Concentration and Wavelength Dependent Refractive Index of Sugar Solution Using Sellmeier Equation. Issue 1 (February 2021) - Misto,; Purwandari, Endhah; Supriyadi,; Arkundato, Artoto; Rohman, Lutfi; Eko Cahyono, Bowo
Abstract: The concentration and wavelength-dependent refractive index of sugar solution have been determined using Sellmeier Equation. The equations describe the refractive index as a function of wavelength parameter. They could be generalized as a function of material concentration by investigating the characteristic of their Sellmeier constants A and B. The three wavelengths used to identify the refractive index of sugar solutions were 455 nm, 525 nm, and 633 nm, while the concentration of the sugar solution ranged from 0 to 40%. This paper reported in this research performed the empirical expression of concentration-dependent of the sugar solution. The A and B Sellmeier constants were the main subjects to be concerned. A constant has a linear relationship with the sugar solution at 15% concentration to 40%. Under a concentration of 15%, the refractive index is quadratic towards engagement. The sellmeier B constant has a quadratic relation characteristic below the attention of 15%. Above 15%, the constant B and concentration of sugar solution were associated with the 4th order polynomial equation.